MODEL RETORIKA AHMAD MUWAFIQ PADA CHANNEL YOUTUBE GUS MUWAFIQ OFFICIAL EDISI 15 NOVEMBER 2020 - Nasichun Amin; Sayidah Afatul Masruroh; Moh. Slamet; Wira Tama; Alfin Miftahul Khoir (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2022)
The focus of this research is to examine So the focus of this research is how to model Ahmad Muwafiq's rhetoric on the Gus Muwafiq Official YouTube channel, November 15 2020 edition. This research approach is a qualitative research. The subject in this research is K.H Ahmad Muwafiq's rhetorical model on the official Gus Muwafiq YouTube channel November 15 2020 edition with a time duration of 1:23.32 and the source of the data obtained temporarily is through: Video and audio recordings from the recitation of the History of the Entry of Islam in the Archipelago edition 15 November 2020 on youtube; b) K.H. Ahmad Muwafiq or better known as Gus Muwafiq as the talented preacher in the video being studied: c) Other preachers as comparative data.Data collection techniques using observation, and documentation methods were carried out directly and supported by in-depth interviews with related parties. Based on the research results obtained, it was concluded that Gus Muwafiq used this rhetorical style well. In terms of the use of language style, in conveying his da'wah material, namely the history of the arrival of Islam in the archipelago, Gus Muwafiq has been able to apply several types of language properly and clearly. Among them are using informal language, using conversational language, using tone-based language style and using sentence-based language style.